Meeting in Belgrade: Lithuania’s aspirations for liberation - Banionis, Juozas (Genocidas ir rezistencija, 2000)
During the meeting in Belgrade in 1977, the signatories to the Final Act of the Conference on Security and Coopera tion in Europe shared their opinions on the implementation of the Helsinki Agreement and discussed ways of developing co-operation between the East and the West. Western countrics expressed their concern for the violation of fundamental human rights in the USSR, in the occupied Baltic countries and in other communist countries. Particular attention was paid to the fact that the Soviets apprehended and persecuted the observers of the implementation of the Helsinki Agreement, to the restriction of the freedom of religion, and measures taken against the reunion of families and travelling abroad. One of the most significant events of the Belgrade meeting was that the participants for the first time after the War, internationally denied the incorporation of the Baltic countries by the USSR.